2021
DOI: 10.3390/jpm11070620
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Circadian Rhythm of Brain Temperature in Traumatic Brain Injury

Abstract: Hypothermia has been used in postoperative management of traumatic brain injury (TBI); however, the rhythmic variation and prognostic value of brain temperature after TBI have never been studied. This study describes diurnal brain temperature patterns in comatose patients with TBI. Mesors of brain temperature, amplitude, and acrophase were estimated from recorded temperature measurements using cosinor analysis. The association of these patterns with clinical parameters, mortality, and functional outcomes in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The peak cBT in sham-operated rats was at 00:16 AM, which is comparable to the findings of a previous study [ 74 ]. In a study comprising 108 patients with moderate-to-severe TBI, 40.7% presented disrupted brain temperature rhythm; however, some patients with normal brain temperature rhythm still exhibited phase shifts [ 13 ]. Only a few studies have investigated the rhythms and acrophases of body or brain temperature in patients after brain injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak cBT in sham-operated rats was at 00:16 AM, which is comparable to the findings of a previous study [ 74 ]. In a study comprising 108 patients with moderate-to-severe TBI, 40.7% presented disrupted brain temperature rhythm; however, some patients with normal brain temperature rhythm still exhibited phase shifts [ 13 ]. Only a few studies have investigated the rhythms and acrophases of body or brain temperature in patients after brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Circadian gene expression within the SCN governs the rhythms of various cellular metabolic processes, neuronal firing, and neuropeptide secretion, which ultimately manifest in physiological and behavioral rhythms [ 9 , 11 , 12 ]. A previous study demonstrated that 40.7% of patients with moderate-to-severe traumatic brain injury (TBI) exhibit disturbed circadian rhythms of brain temperature with a diminished amplitude in the first 72 h following operation [ 13 ]. However, the effects of TBI on the regulation of circadian rhythm-related gene expression in peripheral tissues have not yet been investigated in humans or animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of systemic injury, especially craniocerebral injury, is rising yearly, leading to increasing rates of disability and fatality and bringing a massive burden to individuals, families, and society [31] . Accurate evaluation of traumatic brain injury is of great significance for diagnosis and treatment, and prognosis evaluation [32] . In this study, the predictive ability of serum miR-185-5p level on clinical damage and prognosis of TBI patients was evaluated, and it was found that serum miR-185-5p level was closely related to trauma severity of TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…24 Brain temperature also oscillates, and amplitude of these rhythms may predict survival after traumatic brain injury. 25,26 Here, we review and discuss evidence that these basic physiological rhythms may alter brain homeostasis.…”
Section: Basics Of Circadian Rhythmsmentioning
confidence: 99%